Québec’s Strategy to Incentivize Associate Teacher Mentorship for Practicums Amid a Teacher Shortage - Pattison-Meek, Joanne (International Journal of Education Policy and Leadership, 2025)
A dominant methodology of teacher education programs around the globe is the teaching practicum. Many governments and teacher education programs offer incentives to attract practicing teachers to mentor student teachers during their practicum. Such incentivization strategies are critical during teacher shortages, as mentorship is one means to attract and retain new teachers in the profession. This article analyzes the outcomes of one such initiative: Québec’s Intern Supervision Allowance and subsequent Strategy to Promote the Recognition of School Staff. Drawing on publicly available documents, the analysis highlights regional disparities in how financial incentives are accessed in English-language schools. Urban and suburban boards tend to benefit most, while rural and remote communities gain comparatively little. Recommendations propose more inclusive strategies to incentivize mentorship that are equity-focused and context-aware.